Wild side [large type] - Silver, Elsie (Silver, Elsie. Rose Hill series, 2026)
"She's always dreamed of her wedding day. And those dreams never included saying "I do" to a man she hates. But when Tabitha's nephew's guardianship is contested, she decides she'll do whatever it takes to keep him in Rose Hill. Even if it means marrying the enemy. Rhys Dupris. A man who is secretive, broody, and completely infuriating. A man whose work takes him away for weeks on end and brings him back covered in mysterious bruises--ones he won't talk about. In fact, Tabitha and Rhys barely talk at all. Which would be fine, except when he's not talking, he's staring. And the way he looks at her is borderline indecent. The tension between them has always been palpable. But living under the same roof is a dangerous temptation. Tabitha swore she would never forgive him. But that was before she knew the man behind the mask. The one who's fierce and protective. The one who's gentle and patient. The one who shows up for her and her nephew when they need him most."--